2019
DOI: 10.1097/md.0000000000017734
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of dexketoprofen for migraine attack

Abstract: Background: The efficacy of dexketoprofen for migraine attack remains controversial. We conduct a systematic review and meta-analysis to explore the influence of dexketoprofen supplementation versus placebo on pain control in migraine attack patients. Methods: We search PubMed, EMbase, Web of science, EBSCO, and Cochrane library databases through March 2019 for randomized controlled trials (RCTs) assessing the effect of dexketoprofen supplementation ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The guidelines of the European Federation of Neurological Societies recommend triptans, acetylsalicylic acid, naproxen, ibuprofen, diclofenac, and paracetamol as the first-line medication options. 29 Yang et al 7 reviewed and performed a meta-analysis of five studies published between 2014 and 2016, in which dexketoprofen 50 mg compared with placebo or frovatriptan 2.5 mg combined with dexketoprofen 37.5 mg compared with frovatriptan 2.5 mg plus placebo. They reported that dexketoprofen was a good treatment option in pain relief in patients with migraine, with a reduced need for rescue drugs, and with no significant increase in side effects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The guidelines of the European Federation of Neurological Societies recommend triptans, acetylsalicylic acid, naproxen, ibuprofen, diclofenac, and paracetamol as the first-line medication options. 29 Yang et al 7 reviewed and performed a meta-analysis of five studies published between 2014 and 2016, in which dexketoprofen 50 mg compared with placebo or frovatriptan 2.5 mg combined with dexketoprofen 37.5 mg compared with frovatriptan 2.5 mg plus placebo. They reported that dexketoprofen was a good treatment option in pain relief in patients with migraine, with a reduced need for rescue drugs, and with no significant increase in side effects.…”
Section: Discussionmentioning
confidence: 99%
“…They reported that dexketoprofen was a good treatment option in pain relief in patients with migraine, with a reduced need for rescue drugs, and with no significant increase in side effects. 7 Many studies have investigated the efficacy of mesotherapy on pain relief in health conditions other than migraine. 12 , 14 , 30 , 31 Those studies reported that mesotherapy can be a good treatment option for pain relief when compared to different analgesics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation